Ceramic composite material and preparation method thereof

By using a combination of silicon carbide, boron nitride and silicon dioxide in ceramic materials, combined with modified fillers and a ball abrasive modified by sodium alginate polyphthalate, the problem of poor wear resistance and thermal conductivity when improving strength performance of ceramic materials is solved, and the heat resistance and corrosion resistance are significantly improved, achieving coordinated improvement of material performance.

CN119822841AActive Publication Date: 2025-04-15ZHONGKE BAOLU NEW MATERIALS (LIAONING) CO LTD

Patent Information

Application Number
CN202510325690.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-15
Estimated Expiration
2045-03-19

AI Technical Summary

Technical Problem

When existing ceramic materials improve strength properties, they are prone to poor wear resistance and thermal conductivity, and insufficient heat and corrosion resistance, which limits the efficiency of the product.

Method used

Silicon carbide, boron nitride and silicon dioxide are combined with additives based on modified fillers and ball abrasives based on sodium alginate polymodification to be modified for coordination. Through the coordinated coordination between raw materials, the coordinated improvement of strength, wear resistance and thermal conductivity is achieved, and the heat resistance and corrosion resistance are improved.

Benefits of technology

The coordinated improvement of the strength, wear resistance and thermal conductivity of ceramic composite materials has been achieved, while significantly improving the heat and corrosion resistance of the product and improving the use efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic materials, in particular to a ceramic composite material and a preparation method thereof.The ceramic composite material is prepared from, by weight, 30-35 parts of silicon carbide, 15-20 parts of boron nitride, 10-15 parts of silicon dioxide, 8-11 parts of additive based on modified filler and 7-10 parts of ball milling agent based on sodium alginate reconditioning modification. According to the ceramic composite material, silicon carbide and boron nitride are matched with silicon dioxide, the additive based on the modified filler and the ball-milling agent based on sodium alginate reconditioning modification are blended and coordinated, and through coordination and synergism of the raw materials, the obtained product can achieve coordinated improvement of strength, wear resistance and thermal conductivity; and the product has remarkable heat-resistant and corrosion-resistant stability effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic materials, and in particular to a ceramic composite material and a preparation method thereof. Background Art

[0002] Ceramic composites are a type of composite material that uses ceramic as a matrix and various fibers. The ceramic matrix can be high-temperature structural ceramics such as silicon nitride and silicon carbide. Ceramic-based composites are widely used in liquid rocket engine nozzles, missile radomes, space shuttle nose cones, aircraft brake discs, high-end automobile brake discs, etc., becoming an important branch of high-tech new materials.

[0003] In order to improve the strength performance of the product, the existing ceramic materials easily lead to poor wear resistance and thermal conductivity of the materials. It is difficult to achieve coordinated improvement in strength, wear resistance and thermal conductivity of the products. In addition, the products have poor heat resistance and corrosion resistance, which further limits the efficiency of product use. Summary of the invention

[0004] In view of the defects of the prior art, the object of the present invention is to provide a ceramic composite material and a preparation method thereof to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a ceramic composite material, which comprises the following raw materials in parts by weight: 30-35 parts of silicon carbide, 15-20 parts of boron nitride, 10-15 parts of silicon dioxide, 8-11 parts of additives based on modified fillers, and 7-10 parts of ball mills based on sodium alginate polymodification.

[0006] Preferably, the ceramic composite material comprises the following raw materials in parts by weight: 32.5 parts of silicon carbide, 17.5 parts of boron nitride, 12.5 parts of silicon dioxide, 9 parts of additives based on modified fillers, and 8.5 parts of ball mills based on sodium alginate polymodification modification.

[0007] Preferably, the preparation method of the additive based on modified filler is: S01: stir cordierite in a sufficient amount of 10% by mass potassium permanganate solution, then wash with water, filter, and preheat at 55-60°C for 1h to obtain a preheated cordierite body; S02: mixing double-walled carbon nanotubes and cerium oxide in a weight ratio of 5:2, sintering at 170-180° C. for 1 h, and finally cooling to room temperature to obtain a sintered body; 3-5 parts by weight of the sintered body, 1-3 parts by weight of the silane coupling agent KH550, 5-8 parts by weight of the sodium citrate solution and 2-4 parts of the aluminum silicate fiber are fully blended to obtain a modified solution; S03: stirring the preheated cordierite body and the modified liquid in a weight ratio of 3:5, and completing the stirring to obtain a modified liquid doped with cordierite; S04: The modified solution doped with cordierite and the additive are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain an additive based on a modified filler.

[0008] The additive based on modified filler adopts cordierite as the matrix, and is improved by preheating with potassium permanganate solution to optimize its active efficiency, so as to facilitate the improvement and optimization of the modified liquid. The sintered body in the modified liquid is matched with silane coupling agent KH550, sodium citrate solution and aluminum silicate fiber. Through the coordination and matching between the raw materials, the needle-like structure of aluminum silicate fiber is matched with the sintered body raw material. The double-walled carbon nanotubes and cerium oxide in the sintered body are improved by composite re-sintering. Through the coordination and matching between the raw materials, the coordination and enhancement effect of the cordierite body and the modified is optimized, thereby improving the performance coordination and stability of the system. At the same time, the additive adopts rectorite as the matrix, and is improved by coordinating and matching with dopamine hydrochloride solution, lanthanum oxide, zirconium silicate and nano-titanium dioxide. Through the coordination and matching between the raw materials, the improvement effect of the additive on the modified liquid doped with cordierite is enhanced, and the performance of the product is further improved.

[0009] Preferably, the mass fraction of the sodium citrate solution is 4-7%; the diameter of the double-walled carbon nanotubes is 2-4 nm, the length is 1 μm, and the specific surface area is 375-385 m 2 / g.

[0010] Preferably, the stirring speed of the stirring treatment is 750-800 r / min, and the stirring time is 35-45 min.

[0011] Preferably, the preparation method of the additive is: 5-8 parts by weight of rectorite are added to 10-15 parts by weight of dopamine hydrochloride solution, followed by adding 2-5 parts by weight of lanthanum oxide, 4-7 parts by weight of zirconium silicate and 2-3 parts by weight of nano titanium dioxide, stirring sufficiently, then filtering and drying to obtain an additive.

[0012] Preferably, the mass fraction of the dopamine hydrochloride solution is 2-5%.

[0013] Preferably, the preparation method of the ball mill based on sodium alginate polymodification modification is: S11: mixing sodium alginate and 5% by mass hydrogen peroxide solution in a weight ratio of 2:5, then washing, filtering and drying; The dried sodium alginate powder, chitosan solution and sodium silicate solution are mixed in a weight ratio of 3:5:1 to obtain a sodium alginate compound solution; S12: adding 2-4 parts by weight of magnesium oxide, 3-5 parts by weight of aluminum oxide and 1-3 parts by weight of hydroxyapatite to 5-8 parts by weight of sodium alginate remixing solution and stirring sufficiently to obtain a ball mill modified based on sodium alginate remixing solution.

[0014] The ball mill based on sodium alginate multiple modification is improved by oxidation of sodium alginate, and then blended with chitosan solution and sodium silicate solution, and improved with magnesium oxide, aluminum oxide and hydroxyapatite. Through the co-coordination and coordination between the raw materials, the coordination effect of the ball mill based on sodium alginate multiple modification and the additive based on modified filler is further enhanced, so that the performance of the product is further improved.

[0015] Preferably, the mass fraction of the chitosan solution is 2-5%; the mass fraction of the sodium silicate solution is 5-8%.

[0016] The present invention also provides a method for preparing a ceramic composite material, comprising the following steps: mixing and ball-milling silicon carbide, boron nitride, silicon dioxide, an additive based on a modified filler and a ball mill based on a sodium alginate polymodified modification, at a ball milling speed of 1500 r / min, for 1 hour, and after the ball milling is completed, molding in a mold at a molding pressure of 80 MPa, and finally sintering at 1150° C. for 1 hour, and after the sintering is completed, obtaining a ceramic composite material.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The ceramic composite material of the present invention is blended and coordinated with silicon carbide, boron nitride, silicon dioxide, additives based on modified fillers, and a ball mill based on sodium alginate polymodification. Through the coordinated coordination and synergy between the raw materials, the obtained product can achieve coordinated improvements in strength, wear resistance and thermal conductivity, and the product has significant heat resistance and corrosion resistance stability effects. DETAILED DESCRIPTION

[0018] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] A ceramic composite material of this embodiment includes the following raw materials in parts by weight: 30-35 parts of silicon carbide, 15-20 parts of boron nitride, 10-15 parts of silicon dioxide, 8-11 parts of additives based on modified fillers, and 7-10 parts of ball mills based on sodium alginate polymodification modification.

[0020] The ceramic composite material of this embodiment includes the following raw materials in parts by weight: 32.5 parts of silicon carbide, 17.5 parts of boron nitride, 12.5 parts of silicon dioxide, 9 parts of additives based on modified fillers, and 8.5 parts of ball mills based on sodium alginate polymodification modification.

[0021] The preparation method of the additive based on the modified filler of this embodiment is: S01: stir cordierite in a sufficient amount of 10% by mass potassium permanganate solution, then wash with water, filter, and preheat at 55-60°C for 1h to obtain a preheated cordierite body; S02: mixing double-walled carbon nanotubes and cerium oxide in a weight ratio of 5:2, sintering at 170-180° C. for 1 h, and finally cooling to room temperature to obtain a sintered body; 3-5 parts by weight of the sintered body, 1-3 parts by weight of the silane coupling agent KH550, 5-8 parts by weight of the sodium citrate solution and 2-4 parts of the aluminum silicate fiber are fully blended to obtain a modified solution; S03: stirring the preheated cordierite body and the modified liquid in a weight ratio of 3:5, and completing the stirring to obtain a modified liquid doped with cordierite; S04: The modified solution doped with cordierite and the additive are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain an additive based on a modified filler.

[0022] The mass fraction of the sodium citrate solution in this embodiment is 4-7%; the diameter of the double-walled carbon nanotubes is 2-4 nm, the length is 1 μm, and the specific surface area is 375-385 m 2 / g.

[0023] The stirring speed of the stirring process in this embodiment is 750-800 r / min, and the stirring time is 35-45 min.

[0024] The preparation method of the additive of this embodiment is: 5-8 parts by weight of rectorite are added to 10-15 parts by weight of dopamine hydrochloride solution, followed by adding 2-5 parts by weight of lanthanum oxide, 4-7 parts by weight of zirconium silicate and 2-3 parts by weight of nano titanium dioxide, stirring sufficiently, then filtering and drying to obtain an additive.

[0025] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2-5%.

[0026] The preparation method of the ball mill based on sodium alginate polymodification modification of this embodiment is: S11: mixing sodium alginate and 5% by mass hydrogen peroxide solution in a weight ratio of 2:5, then washing, filtering and drying; The dried sodium alginate powder, chitosan solution and sodium silicate solution are mixed in a weight ratio of 3:5:1 to obtain a sodium alginate compound solution; S12: adding 2-4 parts by weight of magnesium oxide, 3-5 parts by weight of aluminum oxide and 1-3 parts by weight of hydroxyapatite to 5-8 parts by weight of sodium alginate remixing solution and stirring sufficiently to obtain a ball mill modified based on sodium alginate remixing solution.

[0027] The mass fraction of the chitosan solution in this embodiment is 2-5%; the mass fraction of the sodium silicate solution is 5-8%.

[0028] A preparation method of a ceramic composite material in this embodiment includes the following steps: mixing silicon carbide, boron nitride, silicon dioxide, an additive based on a modified filler and a ball mill based on a sodium alginate polymodified modified ball mill, the ball milling speed is 1500r / min, the ball milling is for 1h, after the ball milling is completed, molding in a mold, the molding pressure is 80MPa, and finally sintering at 1150°C for 1h, after the sintering is completed, to obtain a ceramic composite material.

[0029] Example 1 A ceramic composite material of this embodiment includes the following raw materials in parts by weight: 30 parts of silicon carbide, 15 parts of boron nitride, 10 parts of silicon dioxide, 8 parts of additives based on modified fillers, and 7 parts of ball mills based on sodium alginate polymodification modification.

[0030] The preparation method of the additive based on the modified filler of this embodiment is: S01: stir cordierite in a sufficient amount of 10% by mass potassium permanganate solution, then wash with water, filter, and preheat at 55°C for 1h to obtain a preheated cordierite body; S02: mixing double-walled carbon nanotubes and cerium oxide in a weight ratio of 5:2, sintering at 170° C. for 1 h, and finally cooling to room temperature to obtain a sintered body; 3 parts by weight of the sintered body, 1 part by weight of the silane coupling agent KH550, 5 parts by weight of the sodium citrate solution and 2 parts of the aluminum silicate fiber are fully blended to obtain a modified solution; S03: stirring the preheated cordierite body and the modified liquid in a weight ratio of 3:5, and completing the stirring to obtain a modified liquid doped with cordierite; S04: The modified solution doped with cordierite and the additive are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain an additive based on a modified filler.

[0031] The mass fraction of the sodium citrate solution in this embodiment is 4%; the diameter of the double-walled carbon nanotubes is 2nm, the length is 1um, and the specific surface area is 375m 2 / g.

[0032] The stirring speed of the stirring process in this embodiment is 750 r / min, and the stirring time is 35 min.

[0033] The preparation method of the additive of this embodiment is: 5 parts by weight of rectorite are added to 10 parts by weight of dopamine hydrochloride solution, and then 2 parts by weight of lanthanum oxide, 4 parts by weight of zirconium silicate and 2 parts by weight of nano titanium dioxide are added, stirred sufficiently, filtered and dried to obtain an additive.

[0034] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2%.

[0035] The preparation method of the ball mill based on sodium alginate polymodification modification of this embodiment is: S11: mixing sodium alginate and 5% by mass hydrogen peroxide solution in a weight ratio of 2:5, then washing, filtering and drying; The dried sodium alginate powder, chitosan solution and sodium silicate solution are mixed in a weight ratio of 3:5:1 to obtain a sodium alginate compound solution; S12: adding 2 parts by weight of magnesium oxide, 3 parts by weight of aluminum oxide and 1 part by weight of hydroxyapatite to 5 parts by weight of sodium alginate remixing solution and stirring thoroughly to obtain a ball mill modified based on sodium alginate remixing solution.

[0036] The mass fraction of the chitosan solution in this embodiment is 2%; the mass fraction of the sodium silicate solution is 5%.

[0037] A preparation method of a ceramic composite material in this embodiment includes the following steps: mixing silicon carbide, boron nitride, silicon dioxide, an additive based on a modified filler and a ball mill based on a sodium alginate polymodified modified ball mill, the ball milling speed is 1500r / min, the ball milling is for 1h, after the ball milling is completed, molding in a mold, the molding pressure is 80MPa, and finally sintering at 1150°C for 1h, after the sintering is completed, to obtain a ceramic composite material.

[0038] Example 2 A ceramic composite material of this embodiment includes the following raw materials in parts by weight: 35 parts of silicon carbide, 20 parts of boron nitride, 15 parts of silicon dioxide, 11 parts of additives based on modified fillers, and 10 parts of ball mills based on sodium alginate polymodification modification.

[0039] The preparation method of the additive based on the modified filler of this embodiment is: S01: stir cordierite in a sufficient amount of 10% by mass potassium permanganate solution, then wash with water, filter, and preheat at 60°C for 1h to obtain a preheated cordierite body; S02: mixing double-walled carbon nanotubes and cerium oxide in a weight ratio of 5:2, sintering at 180° C. for 1 h, and finally cooling to room temperature to obtain a sintered body; 5 parts by weight of the sintered body, 3 parts by weight of the silane coupling agent KH550, 8 parts by weight of the sodium citrate solution and 4 parts of the aluminum silicate fiber are fully blended to obtain a modified solution; S03: stirring the preheated cordierite body and the modified liquid in a weight ratio of 3:5, and completing the stirring to obtain a modified liquid doped with cordierite; S04: The modified solution doped with cordierite and the additive are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain an additive based on a modified filler.

[0040] The mass fraction of the sodium citrate solution in this embodiment is 7%; the diameter of the double-walled carbon nanotubes is 4nm, the length is 1um, and the specific surface area is 385m 2 / g.

[0041] The stirring speed of the stirring process in this embodiment is 800 r / min, and the stirring time is 45 min.

[0042] The preparation method of the additive of this embodiment is: 8 parts by weight of rectorite are added to 15 parts by weight of dopamine hydrochloride solution, followed by adding 5 parts by weight of lanthanum oxide, 7 parts by weight of zirconium silicate and 3 parts by weight of nano titanium dioxide, stirring thoroughly, filtering and drying to obtain an additive.

[0043] The mass fraction of the dopamine hydrochloride solution in this embodiment is 5%.

[0044] The preparation method of the ball mill based on sodium alginate polymodification modification of this embodiment is: S11: mixing sodium alginate and 5% by mass hydrogen peroxide solution in a weight ratio of 2:5, then washing, filtering and drying; The dried sodium alginate powder, chitosan solution and sodium silicate solution are mixed in a weight ratio of 3:5:1 to obtain a sodium alginate compound solution; S12: adding 4 parts by weight of magnesium oxide, 5 parts by weight of aluminum oxide and 3 parts by weight of hydroxyapatite to 8 parts by weight of sodium alginate compounding solution and stirring thoroughly to obtain a ball mill modified based on sodium alginate compounding solution.

[0045] The mass fraction of the chitosan solution in this embodiment is 5%; the mass fraction of the sodium silicate solution is 8%.

[0046] A preparation method of a ceramic composite material in this embodiment includes the following steps: mixing silicon carbide, boron nitride, silicon dioxide, an additive based on a modified filler and a ball mill based on a sodium alginate polymodified modified ball mill, the ball milling speed is 1500r / min, the ball milling is for 1h, after the ball milling is completed, molding in a mold, the molding pressure is 80MPa, and finally sintering at 1150°C for 1h, after the sintering is completed, to obtain a ceramic composite material.

[0047] Example 3 A ceramic composite material of this embodiment includes the following raw materials in parts by weight: 32.5 parts of silicon carbide, 17.5 parts of boron nitride, 12.5 parts of silicon dioxide, 9 parts of additives based on modified fillers, and 8.5 parts of ball mills based on sodium alginate polymodification modification.

[0048] The preparation method of the additive based on the modified filler of this embodiment is: S01: stir cordierite in a sufficient amount of 10% by mass potassium permanganate solution, then wash with water, filter, and preheat at 57.5°C for 1h to obtain a preheated cordierite body; S02: mixing double-walled carbon nanotubes and cerium oxide in a weight ratio of 5:2, sintering at 175° C. for 1 h, and finally cooling to room temperature to obtain a sintered body; 4 parts by weight of the sintered body, 2 parts by weight of the silane coupling agent KH550, 6 parts by weight of the sodium citrate solution and 3 parts of the aluminum silicate fiber are fully blended to obtain a modified solution; S03: stirring the preheated cordierite body and the modified liquid in a weight ratio of 3:5, and completing the stirring to obtain a modified liquid doped with cordierite; S04: The modified solution doped with cordierite and the additive are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain an additive based on a modified filler.

[0049] The mass fraction of the sodium citrate solution in this embodiment is 5.5%; the diameter of the double-walled carbon nanotubes is 3nm, the length is 1um, and the specific surface area is 380m 2 / g.

[0050] The stirring speed of the stirring process in this embodiment is 770 r / min, and the stirring is performed for 40 minutes.

[0051] The preparation method of the additive of this embodiment is: 6.5 parts by weight of rectorite are added to 12.5 parts by weight of dopamine hydrochloride solution, followed by adding 3.5 parts by weight of lanthanum oxide, 5.5 parts by weight of zirconium silicate and 2.5 parts by weight of nano titanium dioxide, stirring thoroughly, filtering and drying to obtain an additive.

[0052] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3.5%.

[0053] The preparation method of the ball mill based on sodium alginate polymodification modification of this embodiment is: S11: mixing sodium alginate and 5% by mass hydrogen peroxide solution in a weight ratio of 2:5, then washing, filtering and drying; The dried sodium alginate powder, chitosan solution and sodium silicate solution are mixed in a weight ratio of 3:5:1 to obtain a sodium alginate compound solution; S12: adding 3 parts by weight of magnesium oxide, 4 parts by weight of aluminum oxide and 2 parts by weight of hydroxyapatite to 6.5 parts by weight of sodium alginate remixing solution and stirring thoroughly to obtain a ball mill based on sodium alginate remixing modification.

[0054] The mass fraction of the chitosan solution in this embodiment is 3.5%; the mass fraction of the sodium silicate solution is 6.5%.

[0055] A preparation method of a ceramic composite material in this embodiment includes the following steps: mixing silicon carbide, boron nitride, silicon dioxide, an additive based on a modified filler and a ball mill based on a sodium alginate polymodified modified ball mill, the ball milling speed is 1500r / min, the ball milling is for 1h, after the ball milling is completed, molding in a mold, the molding pressure is 80MPa, and finally sintering at 1150°C for 1h, after the sintering is completed, to obtain a ceramic composite material.

[0056] Comparative Example 1 The difference from Example 3 is that no additive based on modified filler is added.

[0057] Comparative Example 2 The difference from Example 3 is that no cordierite-doped modifying liquid is added in the preparation of the additive based on the modified filler.

[0058] Comparative Example 3 The difference from Example 3 is that no preheated cordierite body is added in the preparation of the cordierite-doped modifying liquid.

[0059] Comparative Example 4 The difference from Example 3 is that no modifying liquid treatment is added in the preparation of the modifying liquid doped with cordierite.

[0060] Comparative Example 5 The difference from Example 3 is that no sintered body is added to the modified liquid.

[0061] Comparative Example 6 The difference from Example 3 is that aluminum silicate fiber and silane coupling agent KH550 are not added to the modified liquid.

[0062] Comparative Example 7 The difference from Example 3 is that no additives were added in the preparation of the additive based on the modified filler.

[0063] Comparative Example 8 The difference from Example 3 is that the ball milling agent modified by sodium alginate is not added.

[0064] Comparative Example 9 The difference from Example 3 is that dry sodium alginate powder and sodium silicate solution are not added in the preparation of the ball mill modified based on sodium alginate.

[0065] Comparative Example 10 The difference from Example 3 is that alumina and hydroxyapatite are not added in the preparation of the ball mill based on the sodium alginate polymodification modification.

[0066] The products of Examples 1 to 3 and Comparative Examples 1 to 10 were routinely tested for performance. At the same time, the products were placed at 110° C. for 24 hours, then placed in a 5% hydrochloric acid solution for 24 hours and a 2% sodium hydroxide solution for 24 hours. The above is one cycle. The cycle was repeated 10 times to test the heat resistance and corrosion resistance stability of the products. The test results are shown in Table 1 below. Table 1 is a performance test table of product strength, wear resistance and thermal conductivity; Table 1:

[0067] It can be seen from Comparative Examples 1 to 10 and Examples 1 to 3 that; The product of Example 3 has excellent bending strength, thermal conductivity and wear performance, and the strength, thermal conductivity and wear resistance of the product can be improved in a coordinated manner, and the heat resistance and corrosion resistance stability of the product are remarkable; The product does not contain any of the additives based on modified fillers and the ball milling agent based on sodium alginate, and the performance of the product deteriorates significantly. The performance effect of the product is most significant when the two additives are used in combination. In the preparation of the additive based on the modified filler, the modified liquid doped with cordierite was not added, the preheated cordierite body was not added in the preparation of the modified liquid doped with cordierite, the modified liquid treatment was not added in the preparation of the modified liquid doped with cordierite, the sintered body was not added to the modified liquid, the aluminum silicate fiber and the silane coupling agent KH550 were not added to the modified liquid, and the additive was not added in the preparation of the additive based on the modified filler. The performance of the product has a tendency to deteriorate to varying degrees; The modified liquid obtained by the specific method of the present invention and the preheated cordierite body to obtain the modified liquid doped with cordierite, and the additive based on the modified filler prepared by the additive of the present invention, have the most significant performance effect. At the same time, the inventors of the present invention also found that when the additive is not added in the preparation of the additive based on the modified filler, the performance of the product also shows a more obvious trend of deterioration; In the preparation of the ball mill based on sodium alginate multiple modification, no dry sodium alginate powder and sodium silicate solution, no alumina and hydroxyapatite are added, and the performance of the product has a tendency to deteriorate to varying degrees. The ball mill based on sodium alginate multiple modification obtained by the method of the present invention has the most significant product performance effect.

[0068] Since additives can significantly change the performance of products, further research is needed: The preparation method of the additive is: 6.5 parts by weight of rectorite are added to 12.5 parts by weight of dopamine hydrochloride solution, followed by adding 3.5 parts by weight of lanthanum oxide, 5.5 parts by weight of zirconium silicate and 2.5 parts by weight of nano titanium dioxide, stirring thoroughly, filtering and drying to obtain an additive.

[0069] Experimental Example 1 The only difference from Example 3 is that no lanthanum oxide is added to the additive.

[0070] Experimental Example 2 The only difference from Example 3 is that no nano titanium dioxide is added to the additive.

[0071] Experimental Example 3 The only difference from Example 3 is that zirconium silicate is not added to the additive.

[0072] Experimental Example 4 The only difference from Example 3 is that the dopamine hydrochloride solution is replaced by water.

[0073] Experimental Example 5 The only difference from Example 3 is that no rectorite is added in the additive.

[0074] The test results of the effect of additives on the performance of the product are shown in Table 2 below. Table 2 is a test table of the effect of additives on the performance of the product; Table 2:

[0075] It can be seen from Experimental Examples 1-5 that when no rectorite is added to the additive, the performance of the product has a large trend of change. At the same time, when no zirconium silicate and nano titanium dioxide are added to the additive, the performance of the product has a tendency to deteriorate. When no lanthanum oxide is added to the additive and water is used instead of dopamine hydrochloride solution, the performance of the product has a tendency to deteriorate to varying degrees. The additive obtained by combining rectorite and zirconium silicate with specific raw materials has the most significant product performance effect. Only the product prepared by using the specific raw materials of the present invention has the most significant performance effect. The effects of other methods are not as obvious as those of the present invention.

[0076] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0077] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A ceramic composite material, characterized in that: The ceramic composite material comprises the following raw materials in parts by weight: 30-35 parts of silicon carbide, 15-20 parts of boron nitride, 10-15 parts of silicon dioxide, 8-11 parts of additives based on modified fillers, and 7-10 parts of ball mills based on sodium alginate polymodification.

2. A ceramic composite material according to claim 1, characterized in that: The ceramic composite material comprises the following raw materials in parts by weight: 32.5 parts of silicon carbide, 17.5 parts of boron nitride, 12.5 parts of silicon dioxide, 9 parts of additives based on modified fillers, and 8.5 parts of ball mills based on sodium alginate polymodification modification.

3. A ceramic composite material according to claim 1, characterized in that: The preparation method of the additive based on the modified filler is: S01: stir cordierite in a sufficient amount of 10% by mass potassium permanganate solution, then wash with water, filter, and preheat at 55-60°C for 1h to obtain a preheated cordierite body; S02: mixing double-walled carbon nanotubes and cerium oxide in a weight ratio of 5:2, sintering at 170-180° C. for 1 h, and finally cooling to room temperature to obtain a sintered body; 3-5 parts by weight of the sintered body, 1-3 parts by weight of the silane coupling agent KH550, 5-8 parts by weight of the sodium citrate solution and 2-4 parts of the aluminum silicate fiber are fully blended to obtain a modified solution; S03: stirring the preheated cordierite body and the modified liquid in a weight ratio of 3:5, and completing the stirring to obtain a modified liquid doped with cordierite; S04: The modified solution doped with cordierite and the additive are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain an additive based on a modified filler.

4. A ceramic composite material according to claim 3, characterized in that: The mass fraction of sodium citrate solution is 4~7%; the diameter of double-walled carbon nanotubes is 2~4nm, the length is 1um, and the specific surface area is 375~385m 2 / g.

5. A ceramic composite material according to claim 3, characterized in that: The stirring speed of the stirring treatment is 750~800r / min, and the stirring time is 35~45min.

6. A ceramic composite material according to claim 3, characterized in that: The preparation method of the additive is: 5-8 parts by weight of rectorite are added to 10-15 parts by weight of dopamine hydrochloride solution, followed by adding 2-5 parts by weight of lanthanum oxide, 4-7 parts by weight of zirconium silicate and 2-3 parts by weight of nano titanium dioxide, stirring sufficiently, then filtering and drying to obtain an additive.

7. A ceramic composite material according to claim 6, characterized in that: The mass fraction of dopamine hydrochloride solution is 2~5%.

8. The ceramic composite material according to claim 1, characterized in that: The preparation method of the ball mill based on sodium alginate polymodification modification is as follows: S11: mixing sodium alginate and 5% by mass hydrogen peroxide solution in a weight ratio of 2:5, then washing, filtering and drying; The dried sodium alginate powder, chitosan solution and sodium silicate solution are mixed in a weight ratio of 3:5:1 to obtain a sodium alginate compound solution; S12: adding 2-4 parts by weight of magnesium oxide, 3-5 parts by weight of aluminum oxide and 1-3 parts by weight of hydroxyapatite to 5-8 parts by weight of sodium alginate remixing solution and stirring sufficiently to obtain a ball mill modified based on sodium alginate remixing solution.

9. A ceramic composite material according to claim 8, characterized in that: The mass fraction of the chitosan solution is 2~5%; the mass fraction of the sodium silicate solution is 5~8%.

10. A method for preparing the ceramic composite material according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: mixing silicon carbide, boron nitride, silicon dioxide, an additive based on a modified filler and a ball mill based on a sodium alginate polymodified modification, ball milling at a ball milling speed of 1500 r / min for 1 hour, forming in a mold at a molding pressure of 80 MPa, and finally sintering at 1150° C. for 1 hour to obtain a ceramic composite material.

Citation Information

Patent Citations

  • Ceramic composite material with boron nitrides as matrix

    CN104140267A

  • Radiation-proof healthcare ceramics and preparing method thereof

    CN106348601A

  • Wear-resisting porous ceramic material and preparation method thereof

    CN109320252A

  • Wear-resistant woven ceramic material and preparation method thereof

    CN119176722A

  • Preparation method of bamboo charcoal pot ceramic material

    CN119241243A

Cited By

  • Anti-falling ceramic material, preparation method and application of anti-falling ceramic material in ceramic ornament

    CN120229959A

  • A drop-resistant ceramic material, preparation method and application in ceramic ornaments

    CN120229959B

  • Sulfur autotrophic filler as well as preparation method and application thereof

    CN121181126A

  • High-temperature-resistant insulating ceramic product and preparation method thereof

    CN122464686A

  • A high-temperature-resistant insulating ceramic product and a preparation method thereof

    CN122464686B